Patient centric factors affecting delay in self-diagnosis and seeking medical care for oral cancer: a cross-sectional study - K., Nivedha; P. D., Madankumar; Ranganathan, K.; Narayanan, M. B. Aswath; Kuzhalmozhi, M. (International Journal Of Community Medicine And Public Health, 2024)
Background: Oral cancer is often detected in the advanced stage, with a low survival rate of 5 years and with increase in mortality which, affects patient quality of life. The early diagnosis would reduce the mortality rate and morbidity rate, by bringing a change in the quality of life. Methods: The study utilized convenient sampling method to select the participants. Participants who were diagnosed with oral cancer currently at 3rd and 4th stage. Data collection was done using pre-validated self-administered questionnaire, which was provided to the participants through Google forms. Results: The study demonstrated 43.1% people diagnosed with stage-3 oral cancer had an average delay of 34.6 months and 26% of stage-4 cancer patient had an average delay of 59.9 months to their first visit to treatment center. In this study 34% of the study participants were unaware and had lack of knowledge about oral cancer related symptoms. Self-medications/herbal medications, fear for the treatment, socio-economic factors, COVID-19/ lockdown restriction were also other reasons reported by patients. Conclusions: The prompt treatment is necessary in both advanced cases and early cases of oral cancer. Radiotherapy, chemotherapy, and surgery are all part of the treatment when given timely. Thus, early diagnosis plays a vital role in saving many live.